2014
DOI: 10.1016/j.jaerosci.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of environmental fungal and bacterial bioaerosols during the monsoon season

Abstract: a b s t r a c tRain has been known to remove aerosol particles in air environments. The aerosol particles were captured and removed from the air by rain and the concentration of aerosol particles significantly decreased after rain events. Therefore, rain is regarded as having a good effect on air environments in terms of the respiratory health of the general public. However, humid environments produced by long-term rain events such a monsoon may be a sufficient condition for the growth of microorganisms and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 40 publications
(40 reference statements)
9
37
0
Order By: Relevance
“…During drier years, a higher fungal spores in the air was reported (Pakpour et al, 2015) Rainfall might acts as a vacuum cleaner which clean the air by wet deposition mechanism and thus fungal spores are forced to settle down on the ground or another surfaces (Katial et al, 1997;Polymenakou, 2012).Contrary results were noted by Abu-Dieyeh et al (2010) who recorded the highest colonies count events post the heaviest precipitation and moderate temperature conditions, in Zarqa area, Jordan (Arid Irrano-terranean climate). Heo et al (2014) agreed with Abu-Dieyeh et al, (2010), they found the concentration of fungal bioaersols was much higher during rainy season than in non-rainy days. In such studies, the positive correlation between fungal bioaerosol's concentrations and rain was due to the fact that rain helps creating an environment of required moisture level for better fungal vegetation process, and due to the absence or reduction in solar radiation as well.…”
Section: Meteorological Parameterssupporting
confidence: 91%
“…During drier years, a higher fungal spores in the air was reported (Pakpour et al, 2015) Rainfall might acts as a vacuum cleaner which clean the air by wet deposition mechanism and thus fungal spores are forced to settle down on the ground or another surfaces (Katial et al, 1997;Polymenakou, 2012).Contrary results were noted by Abu-Dieyeh et al (2010) who recorded the highest colonies count events post the heaviest precipitation and moderate temperature conditions, in Zarqa area, Jordan (Arid Irrano-terranean climate). Heo et al (2014) agreed with Abu-Dieyeh et al, (2010), they found the concentration of fungal bioaersols was much higher during rainy season than in non-rainy days. In such studies, the positive correlation between fungal bioaerosol's concentrations and rain was due to the fact that rain helps creating an environment of required moisture level for better fungal vegetation process, and due to the absence or reduction in solar radiation as well.…”
Section: Meteorological Parameterssupporting
confidence: 91%
“…The data measurement of bioaerosol in WWTP showed varying results ( It was found that the concentration of bacteria and fungi was higher during rainy days due to higher air humidity. According to a research, the concentration of bioaerosol in bacteria and fungi during rainy season will be three to seven times higher than that of in normal dry (not raining) condition [13]. As for this research, the average concentration of bioaerosol in bacteria increased three to fifteen times during the rainy season and two to five times in fungi during the dry season.…”
Section: Concentration Of Bioaerosol In the Surrounding Wwtpmentioning
confidence: 52%
“…We can normally observe clean ambient air environments and a clearer sky after rain events. However, a recent study reported an interesting and unexpected experimental result (Heo et al, 2014). As expected, rain decreased the PM10 concentration of the ambient environments; however, rain events increased the concentrations of airborne microorganisms in ambient air environments.…”
Section: Introductionmentioning
confidence: 69%
“…Airborne microorganisms, termed bioaerosols, are a type of aerosol particle (Hinds, 1999;Lee, 2011), but they did not follow the behaviors of other non-biological aerosol particles during rain events. The study showed that the concentrations of culturable fungal and bacterial bioaerosols during rain events were seven times and three times higher than at times without rain, respectively (Heo et al, 2014). In the same period, PM10 concentrations strongly decreased during rain events.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation